Petrogenesis and geodynamic significance of the Ganhe Formation lavas, eastern Great Xing'an Range, China : Evidence from geochemistry and geochronology - A‐lei Gu; Jing‐gui Sun; Ling‐an Bai; Yong Zhang; Pei‐long Cui; Peng Chai; Ke‐qiang Zhao; Qing‐long Sun; Liang Ren; Yan‐jun Chen; Jun‐quan Zhu (Island Arc, 2016)
Mesozoic volcanic rocks are widespread throughout the Great Xing'an Range of northeastern China . However, there has been limited investigation into the age and petrogenesis of the Mesozoic volcanics in the eastern Great Xing'an Range. According to our research, the volcanic rocks of the Dayangshu Basin, eastern Great Xing'an Range are composed mainly of trachybasalt, basaltic andesite, and basaltic trachyandesite, with minor intermediate–basic pyroclastic rocks. In this study, the geochemistry and geochronology of the Mesozoic volcanic rocks are presented in order to discuss the petrogenesis and tectonic setting of the Ganhe Formation in the Dayangshu Basin. Zircon U–Pb dating by laser ablation inductively coupled plasma–mass spectrometry indicates that the Mesozoic lavas formed during the late Early Cretaceous (114.3–108.8 Ma). This suite of rocks exhibits a range of geochemical signatures indicating subduction‐related genesis, including: (i) calc‐alkaline to high‐K calc‐alkaline major element compositions; (ii) enrichment of large ion lithophile elements (e.g. Rb, Ba, K) and light rare earth elements (LREEs/HREEs =7.33–9.85); and (iii) weak depletion in high field strength elements (e.g. Nb, Ta, Ti). Furthermore, Sr–Nd–Pb isotopic data yield initial 87 Sr/ 86 Sr values of 0.70450–0.70463, positive ε Nd (t) values of +1.8 to +3.3, and a mantle‐derived lead isotope composition. Combined with the regional tectonic evolution, the results of this study suggest that the Ganhe Group lavas are derived from decompression melting of a metasomatized (enriched) lithospheric mantle, related to asthenospheric upwelling, which resulted from lithospheric mantle delamination and produced extension of the continental margin following the subduction of the Paleo‐ Pacific Plate.